2021
DOI: 10.1177/09673911211054261
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of bio-composites using senegalia catechu resin

Abstract: Owing to the increase in demand on bio-degradable materials, the present researches focus on the development of materials with full degradability. This research is intended to develop a bio-resin–based composite from senegalia catechu gum for light load automotive applications. The bio-resin obtained from the plant is processed with commercial polyester in order to make it as a functional resin for composite preparation. The synthesized resin is made in the form of structural materials by adding jute reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The responses have been configured to minimize between the minimum and maximum readings, whereas the input parameters have been adjusted to a range between minimum and maximum values. The ideal condition with a desirability close to 1 was chosen among the list of optimum conditions when optimization was done using the desirability approach [50][51][52]. The results show that the best conditions are a load of 5 N, a speed of 3 m/s, a sliding distance of 1000 m, and the selection of sample 3, with a maximum desirability of 0.942.…”
Section: Resultsmentioning
confidence: 99%
“…The responses have been configured to minimize between the minimum and maximum readings, whereas the input parameters have been adjusted to a range between minimum and maximum values. The ideal condition with a desirability close to 1 was chosen among the list of optimum conditions when optimization was done using the desirability approach [50][51][52]. The results show that the best conditions are a load of 5 N, a speed of 3 m/s, a sliding distance of 1000 m, and the selection of sample 3, with a maximum desirability of 0.942.…”
Section: Resultsmentioning
confidence: 99%
“…In FTIR amide groups were increased and thermal stability also improved. Vinayagamoorthy and Venkatakoteswararao 22 development and characterization of bio-composites using senegalia catechu resin. They reported a positive sign in bio resin-based composites to have superior mechanical and thermal characteristics as compared to synthetic composites.…”
Section: Introductionmentioning
confidence: 99%
“…14 Bio-polymer composites which are more environmentally friendly and recyclable materials offer less weight, high strength, anti-corrosion, etc. 15,16 The plant resins are such as tamarind, 17 soy protein, 18 wheat protein, 19 banana sap, 20 corn, 21 catechu, 22 karaya, 23 guar, 24 kondagogu gum, etc. 2528 These resins have resulted in improved mechanical properties and reduced overall weight, which enhances the ease of production and decreases the cost.…”
Section: Introductionmentioning
confidence: 99%
“…They have indicated that non -woven veils could affect the tolerance of laminates under hot -wet conditions. Vinayagamoorthy et al [14] have made an investigation to study the characteristics of composites employing natural resin. They have reported that the fiber orientation and fiber composition have played a vital role in deciding the strength characteristics of specimen laminates.…”
Section: Introductionmentioning
confidence: 99%